Can We Identify Abnormalities in Normal Appearing White Matter of Patients with Clinically Isolated Syndrome? Use of Magnetization Transfer Imaging - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2014)
Objective: To reveal hidden pathological distortions in normal appearing white matter (NAWM) and corpus callosum (NACC) of patients with clinically isolated syndrome (CIS) using advanced magnetic resonance imaging (MRI) sequences. Methods: Twelve patients with CIS and 12 age and sex-matched healthy individuals were enrolled in the study. Duration of the disease and first and last Expanded Disability Status Scale (EDSS) scores were recorded. In both groups, SE T1 WI, PD WI, SE T2 WI, FLAIR, T1-W magnetization transfer imaging (MTI), GE T2 WI, GE T2-W MTI, diffusion weighted (DWI) and diffusion tensor imagings (DTI) were performed and used for obtaining apparent diffusion coefficient (ADC), fractional anisotropy (FA), T1 magnetization transfer ratio (MTR), and GE MTR in each group. Values obtained by measurements of these parameters from periventricular NAVW (4 locations) and NACC (2 locations) were compared between patient and control groups. Duration of the disease, and first and last EDSS scores were compared with T1 MTR values. Statistical significance was set as p < 0.05. Results: Mean T1 MTR values were significantly different at all locations, while GE MTR, ADC and FA values were not. Disease duration was found to have a moderate negative significant correlation with T1 MTR values at the splenium of the corpus callosum (r: -0.653, p: 0.021). Conclusions: We believe that T1-W MTI and T1 MTR will be of benefit in demonstrating subtle pathological distortions of the NAWM and NACC of patients with CIS.
Keywords: Multiple sclerosis; clinically isolated syndrome; white matter; magnetic resonance imaging; magnetization transfer imaging; diffusion weighted imaging; diffusion tensor imaging; REMITTING MULTIPLE-SCLEROSIS; TRANSFER MRI; HISTOGRAM ANALYSIS; PROGNOSTIC VALUE; TRANSFER RATIO; GRAY-MATTER; BRAIN MRI; FOLLOW-UP; DAMAGE; RESONANCE